2022
DOI: 10.1186/s40360-022-00553-x
|View full text |Cite
|
Sign up to set email alerts
|

Bcl-xL DNAzymes promote radiosensitivity and chemosensitivity in colorectal cancer cells via enhancing apoptosis

Abstract: Background RNA-cleaving deoxyribozymes (DNAzymes) are catalytic deoxyribonucleic acid molecules that have become a promising new class of gene suppressors by binding and cleaving target mRNA. This study investigated whether DNAzymes targeting Bcl-xL enhanced the effectiveness of radiotherapy and chemotherapy in colorectal cancer (CRC) cells. Methods Two types of CRC cells, SW480 and SW837, were transfected with five DNAzymes. Cell viability, Bcl-xL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Vitamin D has been found to enhance cisplatin chemotherapy and is suggested to be supplied during chemotherapy [ 35 ]. Through enhancing apoptosis, multiple molecules (e.g., Bcl-xL DNAzymes) promote radiosensitivity and chemosensitivity in cancer cells [ 36 ]. Recently, Jaidee et al showed that the inhibition of fibroblast growth factor receptor 2 enhances chemosensitivity to gemcitabine in cholangiocarcinoma [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D has been found to enhance cisplatin chemotherapy and is suggested to be supplied during chemotherapy [ 35 ]. Through enhancing apoptosis, multiple molecules (e.g., Bcl-xL DNAzymes) promote radiosensitivity and chemosensitivity in cancer cells [ 36 ]. Recently, Jaidee et al showed that the inhibition of fibroblast growth factor receptor 2 enhances chemosensitivity to gemcitabine in cholangiocarcinoma [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, these Bcl-xL targeting enzymes (DT882, DT883, and DT884) suppressed the expression of Bcl-xL and made RC cells more sensitive to 5-FU and radiotherapy. 82 , 83 …”
Section: Mechanisms Of Sensitizing Tumors To Radiationmentioning
confidence: 99%
“…Yu et al used DNAzymes to downregulate Bcl-xL mRNA expression to enhance the radiosensitivity and chemosensitivity of the chemotherapeutic drug Fluorouracil (5-FU). [183] Prodrug-mediated tumor in situ activation combined with DNAzyme-mediated gene therapy is a new synergistic therapeutic strategy. A biMOF-encapsulated DNAzyme system was developed to activate anticancer drugs in cancer cells and deplete EGR-1 mRNA mediated by DNAzymes (Figure 11F).…”
Section: Dnazymes In Chemotherapymentioning
confidence: 99%
“…used DNAzymes to downregulate Bcl‐xL mRNA expression to enhance the radiosensitivity and chemosensitivity of the chemotherapeutic drug Fluorouracil (5‐FU). [ 183 ]…”
Section: Recent Synergistic Strategies To Improve Dnazyme Therapeutic...mentioning
confidence: 99%